A Study of the Belief on Evil in Buddhism of the High School Students in Doi Sake Witthayakhom School Doi Saket District Chiang Mai Province - Ṭhitaviriyo (Intranakhachai), Phramaha Krit (MCU Haripunchai Review, 2021)
This thesis aims to examine the fundamentals of Buddhism affecting the level of beliefs in evils among the high school students of Doi Saket Witthayakhom School, Doi Saket District Chiang Mai Province. This research carried out through a quantitative research method. All data were analyzed through frequency, percentage, mean and standard deviation and presented them in a descriptive table. The results of the study revealed the general behavior of the students’ family of Buddhism was at a certain level of practice, and it gains an average of 2.82. For example, parents instructed them to abstain from violating the Five Precepts because it was the cause of allowing evil. In the parenting aspect, overall, there was a level of practice at the Sometime Level; it gains an average of 3.43. For example, a student’s parents would scold and punish them as soon as they made a mistake without communicating the opportunity to them to explain the reason for the offense. On the Buddhist behavior in schools, on average, it showed there was the practice at the Sometime Level, and it gains an average of 3.48. In terms of bodily actions, it overall reported the average of 4.34. They believed in evil, but remained in doubt. When considered at each question, it found they believed in evil, however, they produce questions about those evils. On the verbal action, it gains the average of 4.13, they believed in evil but however had doubts, considering on each question, it showed that they believed in evil but still had all doubts. On the mental action, on average of 4.26, they accept a belief in evil but remain in doubt. When considering on each of the questions, it showed they had doubts on every list. Broadly, it showed that high school students at Doi Saket Witthayakhom School believed in evil at a moderate level.